Experience of an interactive, autism-specific online professional development training and support programme delivered to regional and remote areas. (3rd April 2023) - Johnsson, Genevieve; Lincoln, Michelle; Bundy, Anita; Bulkeley, Kim
ABSTRACT: Training and support will be vital in developing and maintaining a skilled disability workforce in the roll-out of individualised disability funding across Australia. Technology has the potential to deliver training and support that is more accessible and cost-efficient in geographically isolated regions. The current qualitative study explored participants' experience of an autism-specific webinar and individual online support programme delivered to a range of early childhood staff in regional and remote areas. Researchers used purposive sampling to select and interview 11 participants enrolled in the training and support programme. Rigour and trustworthiness of the data were enhanced using member checking and a data analysis check on 20% of the transcripts. Several categories of responses were identified under three broad themes; impact of the training programme, interaction with technology, and barriers to access. Findings indicated that the programme had a positive impact on access to autism-specific learning and support. The interactive nature of webinars and individual online consultations (synchronous learning) was highly valued; however, barriers including extensive travel and busy caseloads resulted in participants relying on recorded webinars (asynchronous learning). Findings from the current study will inform the development of future training programme at an individual, organisational and policy level.